Performance of ternary Cu-Ga2O3-ZrO2 catalysts in the synthesis of methanol using CO2-rich gas mixtures - Fornero, Esteban Luis (2013)
The synthesis of methanol via catalytic hydrogenation of carbon oxides was evaluated in two groups of Cu-GaOx/ZrO2 ternary catalysts containing 2 wt% Cu. Copper was incorporated in the first group either by incipient wetness (IW) or by ion exchange (IE), both on the pure oxides (Ga2O3 y ZrO2) and the x-Ga2O3/ZrO2 mixed oxides (where x = 1, 6 or 9 wt% Ga2O3). In a second group of materials galia was incorporated onto Cu-ZrO2 previously dried or dried/calcined. The catalytic evaluations were performed in a tubular microreactor at 3 MPa, 523 K, GHSV = 20000 h-1 using two different gas mixtures. The first mixture contained CO2 and CO (M1: H2/CO2/CO = 75/22/3), while in the second one carbon monoxide was replaced by He (M2: H2/CO2/He = 75/22/3). The yield to methanol was progressively higher with gallia loading, but the best catalyst tested had an intermediate loading of Ga2O3 deposited onto a dried and calcined Cu/ZrO2 precursor which was obtained, in turn, by ion exchanging copper nitrate to the zirconia. The catalysts for which gallium was added to the dried and calcined IE Cu/ZrO2 precursor were the most stable.